PROMOSI OBJEK WISATA ALAM MAYANG PEKANBARU PADA MASA PANDEMI COVID-19 - Fenny Lorensia; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The tourism sector is a sector that has the potential to be developed as a source of regional income. The program for developing and utilizing regional tourism resources and potential is expected to contribute to economic development since the Covid-19 hit, a lot of tourism has been lost due to adverse impacts. One of the attractions that is still running well in the midst of the COVID-19 pandemic is Alam Mayang Pekanbaru which is a tourist attraction suitable for families and a place to spend time with groups of visitors who want to relax and enjoy the scenery like being at home. However, this tourist attraction that is known by the public does not yet have adequate promotion and tourism targets. Promotion is a one-way flow of information or persuasion or made to direct an organization or person to actions that create exchanges in marketing by planning and implementing good promotional strategies for both income and visits to the Alam Mayang Pekanbaru tourist attraction. Therefore, this study aims to to find out the Strategy for Promotion of the Pekanbaru Mayang Nature Tourism Object during the Covid-19 Pandemic. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and documentation. The Promotion Strategy includes reporting on conditions carried out in advertising, sales promotion, public relations and personal selling. Based on the results of the research that has been carried out, for the entirety of the results of observations and interviews, it can be concluded that the Promotion Strategy for the Pekanbaru Mayang Natural Tourism Object during the Covid-19 Pandemic has not fully worked out as targeted. Keywords: Promotion Strategy, Covid-19